MTOR signalling and cellular metabolism are mutual determinants in cancer. Issue 12 (December 2018) - Mossmann, Dirk; Park, Sujin; Hall, Michael
Abstract Oncogenic signalling and metabolic alterations are interrelated in cancer cells. mTOR, which is frequently activated in cancer, controls cell growth and metabolism. mTOR signalling regulates amino acid, glucose, nucleotide, fatty acid and lipid metabolism. Conversely, metabolic inputs, such as amino acids, activate mTOR. In this Review, we discuss how mTOR signalling rewires cancer cell metabolism and delineate how changes in metabolism, in turn, sustain mTOR signalling and tumorigenicity. Several drugs are being developed to perturb cancer cell metabolism. However, their efficacy as stand-alone therapies, similar to mTOR inhibitors, is limited. Here, we discuss how the interdependence of mTOR signalling and metabolism can be exploited for cancer therapy. This Review discusses the interdependencies of mTOR signalling and metabolism pathways in cancer and how metabolic reprogramming in response to changes in mTOR signalling and vice versa can sustain tumorigenicity. The authors highlight therapeutic opportunities when targeting metabolism and mTOR.